Foreign Aid and Intergenerational Mobility in Africa - (:unkn) unknown (My University, 2021)
While there is extensive literature examining the growth and development effects of foreign aid, very little attention has been paid to its potential impact on social mobility. Thus, this paper provides the first empirical evidence on the effect of foreign aid on intergenerational educational mobility in Africa. Drawing on a sample of 28 countries over the period 1970-2010 and using the popular and wellknown probit estimator, we find strong evidence that foreign aid raises the likelihood of experiencing upward educational mobility in the region, while the probability of downward educational mobility tends to be lower in countries that receive a high level of foreign aid. These effects mainly operate through the increased financing for education, the improved education system, and policy, as well as improved education conditions. More interestingly, focusing on the sectoral decomposition of total aid receivedi.e., education sector versus the rest of the economy-, the study highlights that foreign aid to the education sector tends to increase the likelihood of upward educational mobility, contrary to aid allocated to the rest of the economy. Our finding suggests that foreign aid has contributed to improving social mobility in African countries.
Keywords: African Research